“Eu era o “nerdezinho” da sala, e a escola nunca entendeu que eu estava em pânico...”: (inter)locuções, subjetividades e diferenças da pessoa autista no espaço escolar - Guimarães, Juliana Graziella Martins (2018)
The present research of qualitative nature has the intention of investigating the expressions of mild autistics in the interaction with other subjects in the school space, as well as discuss the themes related to sexuality and differences in the construction of the subjectivities of these people, having as a theoretical methodological perspective post -structuralist reference, of foucaultian inspiration. The selected participants were those who, within the Autism Spectrum Disorder (ASD), are mild level. The way of obtaining the empirical material was through an open interview, from the research drawing oral history of life. A script was drawn up to guide the reports and when necessary to start the conversation with the interviews but let them tell their life story in a freeway. Voice recording and/or field diaries were used as resources, followed by transcription of the reports that were transformed into first person text. The choice of use of the resource was made at the time of the interview, using the resources that was most convenient for the research participant.